Using Maqasid Shariah to Utilize the Contemporary Waqf: Implementing Artificial Intelligence as an Example - Saeed Ahmed Saleh Farag; Mahmoud Mohamed Ali Mahmoud Edris; Yusuf Sani Abubakar; Ahmed Mohammed Azab Mousa (Kurdish Studies, 2024)
Non-Indexed Publication